2019
DOI: 10.26858/jppk.v5i2.10549
|View full text |Cite
|
Sign up to set email alerts
|

Academic self-concept, teacher’s supports and student’s engagement in the school

Abstract: This research aims to examine the role of academic self-concept as the moderate variable on the relationship between teacher's support and students' engagement in school. This research uses qualitative through the correlational method. Students' engagement is measured by the student's engagement at school questionnaires (SESQ). While the teacher's support is measured by the perceived teacher academic support scale (PTASS). Academic self-concept is a moderate variable that is measured by using the academic self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
7
0
5
Order By: Relevance
“…Items were drawn from existing research, increasing the content validity of the measure. 42 SESQ contains four composites (i.e., student engagement in the schools, motivational beliefs, social-relatedness contexts, student outcomes). For the purposes of this study, only the composite of Student Engagement in Schools (SESQ-ENG; 33 items) was utilized to measure indicators of engagement (i.e., affective, behavioral, and cognitive).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Items were drawn from existing research, increasing the content validity of the measure. 42 SESQ contains four composites (i.e., student engagement in the schools, motivational beliefs, social-relatedness contexts, student outcomes). For the purposes of this study, only the composite of Student Engagement in Schools (SESQ-ENG; 33 items) was utilized to measure indicators of engagement (i.e., affective, behavioral, and cognitive).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, this scale has a good reported overall internal consistency (α > 0.70) 43 and the score for validity is 0.45. 42 …”
Section: Methodsmentioning
confidence: 99%
“…In the same line with the current study, ( Galugu 2019) examined the role of academic self-concept as the moderate variable on the relationship between teacher's support and students' engagement in school. The results showed that the relationship between the teacher's support and students' engagement in school is increasingly strengthened by the presence of academic self-concept as a moderated variable.…”
Section: Discussionmentioning
confidence: 64%
“…Hal ini sejalan dengan kriteria konsep diri akademik, individu akan lebih menghargai dirinya sendiri jika lingkungan turut memberikan dukungan secara positif seperti prestasi akademik yang dihargai orangtua, guru atau teman sekelas (Jevtić & Mikanović, 2017). Dukungan emosional dari dosen kepada mahasiswa baik dalam proses pembelajaran dan interaksi di luar pembelajaran, dapat membentuk konsep diri akademik siswa yang positif serta keterlibatan mahasiswa yang positif pula (Galugu & Samsinar, 2019;Lietaert, Roorda, Laevers, Verschueren, & De Fraine, 2015).…”
Section: Pembahasanunclassified
“…Hal ini dikarenakan konsep diri akademik dapat mendorong kepada perilaku positif melalui keterlibatannya dalam tugas-tugas akademik, mengatur pembelajaran dan terlibat dalam menentukan strategi pembelajaran yang efektif dalam aktivitas akademik guna mencapai prestasi akademik yang diharapkan. Mahasiswa yang tidak mengetahui kemampuan akademiknya sendiri cenderung akan menunjukkan sikap yang pesimis, kurang percaya diri, serta memiliki minat atau motivasi yang lebih rendah sehingga seringkali tidak mampu dalam menjalankan kegiatan akademik (Ebrahim, El, Rady, Kabeer, & El-nady, 2016;Galugu & Samsinar, 2019;Huang, 2011).…”
Section: Pembahasanunclassified